2010
DOI: 10.1176/appi.ajp.2009.08081167
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mu-Opioid Receptor Variants and Response to Citalopram Treatment in Major Depressive Disorder

Abstract: Objective-Because previous preclinical and clinical studies have implicated the endogenous opioid system in major depression and in the neurochemical action of antidepressants, the authors examined how DNA variation in the μ-opioid receptor gene may influence population variation in response to citalopram treatment. Method-A total of 1,953 individuals from the Sequenced Treatment Alternatives to RelieveDepression (STAR*D) study were treated with citalopram and genotyped for 53 single nucleotide polymorphisms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 29 publications
(33 reference statements)
0
35
1
Order By: Relevance
“…Indeed, the opioid system may also be important in the pathophysiology and treatment of depression. 55,56 As the search for novel antidepressants continues, researchers have turned towards the opioid system for potential therapeutic targets, with the goal of finding an effective antidepressant compound, sans addiction potential. One such Alkermes compound-ALKS 5461-combines buprenorphine (a μ-opioid receptor partial agonist and functional kappa-opioid receptor antagonist) with samidorphan (a potent μ-opioid receptor antagonist) in an attempt to create a functional kappa receptor antagonist.…”
Section: Anticholinergic Modulatorsmentioning
confidence: 99%
“…Indeed, the opioid system may also be important in the pathophysiology and treatment of depression. 55,56 As the search for novel antidepressants continues, researchers have turned towards the opioid system for potential therapeutic targets, with the goal of finding an effective antidepressant compound, sans addiction potential. One such Alkermes compound-ALKS 5461-combines buprenorphine (a μ-opioid receptor partial agonist and functional kappa-opioid receptor antagonist) with samidorphan (a potent μ-opioid receptor antagonist) in an attempt to create a functional kappa receptor antagonist.…”
Section: Anticholinergic Modulatorsmentioning
confidence: 99%
“…Some data have shown that opioids produce antidepressant effects and those dual action antidepressants such as venlafaxine and duloxetine can produce analgesic action [45]. Furthermore, mu receptor has also been genetically associated with citalopram response in MDD [46] while antidepressant effects of venlafaxine are abolished in mu opioid receptor knockout mice [47]. Finally, studies in mice model of depression have shown that the combination between classical monoaminergic antidepressants and opioid receptor agonists can produce synergistic antidepressant effects [48].…”
Section: Activity At Opioid Receptorsmentioning
confidence: 99%
“…The activation of sigma-1 receptors appear to be involved in the enhancement of the prefrontal dopaminergic neurotransmission and in the antidepressant effects mediated by some drugs such as fluvoxamine, fluoxetine, citalopram, sertraline, clorgyline, and imipramine [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. In an open study, a small sample of depressed patients was treated with JO-1784, a sigma-1 receptor agonist, which induced a 50% reduction of intensity of depressive symptoms on the Hamilton depression scale.…”
Section: Activity At Sigma-1 Receptorsmentioning
confidence: 99%
“…In humans, depressed individuals and healthy comparison subjects exhibited different patterns of mu opioid receptor availability in emotionally neutral and sad states (54), supporting a role for opioids in mood. In addition, polymorphisms in the mu opioid receptor gene were associated with citalopram response in STAR*D (55).…”
Section: Opioid-based Treatmentsmentioning
confidence: 99%